Pendidikan Kewirausahaan Berbasis Pengalaman Praktis: Sebuah Pendekatan Kolaborasi Universitas Dan Sekolah Dasar - Dewi, Lati Sari; Barkah, Risman (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
Implementation of Community Service at SDN Panumbangan 1, Panumbangan District, Ciamis Regency aimed to develop entrepreneurship education based on practical experience through collaboration between the university and the elementary school. This activity was designed to introduce entrepreneurship concepts to students from an early age by integrating basic entrepreneurial theories with hands-on practice. The community service program was carried out through interactive teaching methods, group discussions, and direct practice in designing simple business ideas. The results showed an increased understanding among students of fundamental entrepreneurship concepts, enhanced creativity in generating business ideas, and improved teamwork skills. Evaluations indicated that the program successfully fostered entrepreneurial interest among students and improved their critical thinking and problem-solving abilities. The sustainability of this program requires further integration into the elementary school curriculum and continuous training for educators to support more effective entrepreneurship implementation.